Behavioral community psychology in the Amazon rainforest: Suggestions for when behavior analysts meet alterity - Silva, Felipe Bulzico da [UNESP]; Leugi, Guilherme Bergo (Springer, 2022)
The present paper aimed to discuss and interpret methodological issues and contributions arising mainly from professional field work conducted by a behavior analyst working as a behavioral community psychologist in the Amazon rainforest, in northern Brazil. We looked at such a professional's day-to-day circumstances and challenges within a semi-isolated Indigenous community, and systematized impressions and implications for practice with diverse verbal communities and social groups. We believe that looking at experience with those specific social contexts enables us to critically examine behavior analysis community practice more generally. We provided examples of said practices and examined their explicit and more subtle consequences. In light of that, we discussed features of a collaborative methodological stance while working in the field that we wish to foster and encourage. We conclude by pointing out advantages of more in-depth and intensive relational methods for behavior analysts in community practice.
Keywords: Intensive methods; Collaborative methods; Behavior analysis; Community psychology; Alterity; Cultural practices